2014
DOI: 10.1371/journal.pone.0098540
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolomics Profiling for Identification of Novel Potential Markers in Early Prediction of Preeclampsia

Abstract: Objective The first aim was to investigate specific signature patterns of metabolites that are significantly altered in first-trimester serum of women who subsequently developed preeclampsia (PE) compared to healthy pregnancies. The second aim of this study was to examine the predictive performance of the selected metabolites for both early onset [EO-PE] and late onset PE [LO-PE].MethodsThis was a case-control study of maternal serum samples collected between 8+0 and 13+6 weeks of gestation from 167 women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 48 publications
2
80
1
Order By: Relevance
“…Alterations in metabolic substrates and a consequent energy crisis have been thought to trigger the clinical manifestations of PE. Although the metabolite profile of PE has been studied in various biosamples, including peripheral blood, urine and amniotic fluid [30][31][32], the metabolite characteristics of the placenta in PE are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in metabolic substrates and a consequent energy crisis have been thought to trigger the clinical manifestations of PE. Although the metabolite profile of PE has been studied in various biosamples, including peripheral blood, urine and amniotic fluid [30][31][32], the metabolite characteristics of the placenta in PE are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…They have, however reported significant differences in the blood or urine metabolome of pregnant women who have or are destined to develop PE. 16,17,[29][30][31][32] The different biomarkers reported are partly a consequence of the different metabolomic platforms used (ie, NMR vs mass spectrometry), which tend to identify different kinds of compounds. Variation in results can also be ascribed to different specimen types, gestational age at testing, category, and indeed, definitions of PE used.…”
Section: Commentmentioning
confidence: 99%
“…49 Kuc et al reported 308 lower levels of asparagine in pre-eclamptic pregnant women. 50 Glutamate and aspartate are the only AA 309 which are not actively transported across the placenta 48 and glutamate from the fetal circulation is taken 310 up into the placenta. 51 Thus, higher maternal levels of glutamate are not depleted via fetal transport 311 similar to other AA but likewise, higher maternal glutamate levels may not influence fetal growth.…”
mentioning
confidence: 99%